Analisis Penerapan Sistem Tanggap Darurat Kebakaran di RS X Kota Dumai - Annisa Wahdania; Endang P Rahayu; Herman M Purwonegoro (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Fire hazards are one of the potential disasters in hospitals that can threaten both human safety and assets. This study aims to analyze the implementation of the fire emergency response system at X Hospital Dumai City. The study employed a qualitative case study design. The main informants were members of the Hospital Occupational Safety and Health Committee (K3RS), supported by hospital staff as secondary informants. Data were collected through in-depth interviews, direct observation, and document review, then analyzed using triangulation techniques. The findings revealed several issues: (1) the installation of active fire protection systems (alarms, detectors, sprinklers) was not yet optimal, (2) the hospital lacked certified fire safety specialists, (3) no schedule for fire training and drills was available, and (4) several fire extinguishers were found with abnormal pressure. A fishbone analysis identified contributing factors, including man (lack of awareness and specialists), money (limited budget allocation), material (inadequate fire protection facilities), and method (absence of training schedules). The proposed interventions include hiring fire safety specialists, allocating budget for improving and adding fire protection facilities, installing emergency lighting on escape stairs, replacing damaged extinguishers, and conducting regular fire drills at least once a year. This study recommends that the hospital strengthen its fire emergency response system through improved facilities, regular training, and continuous supervision.